2010
DOI: 10.1509/jmkr.47.5.883
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Social Interactions in Physician Prescription Behavior: The Role of Opinion Leaders

Abstract: The authors quantify the impact of social interactions and peer effects in the context of physicians’ prescription choices. Using detailed individual-level prescription data, along with self-reported social network information, the authors document that physician prescription behavior is significantly influenced by the behavior of research-active specialists, or “opinion leaders,” in the physician's reference group. The authors leverage a natural experiment in the category: New guidelines released about the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(55 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…Inversely, the target regarding the second type of objective might be most influenced by the GP’s social interactions with specialists or “opinion leaders” because, especially when changes occur in the therapeutic environment (e.g., pharmaceutical innovations or introduction of new guidelines), GPs solicit the opinions of specialists when making prescribing decisions [20]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inversely, the target regarding the second type of objective might be most influenced by the GP’s social interactions with specialists or “opinion leaders” because, especially when changes occur in the therapeutic environment (e.g., pharmaceutical innovations or introduction of new guidelines), GPs solicit the opinions of specialists when making prescribing decisions [20]. …”
Section: Discussionmentioning
confidence: 99%
“…In particular, the interaction with specialists may emphasize the benefits of innovation at the expense of the GP’s goals associated with their gatekeeping function and norms (e.g., implement prescriptive standards); Nair and colleagues’ [20] concept of “asymmetric peer effect” intuitively suggests the dynamics associated with this type of social interaction. According to this line of reasoning, the information and advice flowing from a heterogeneous personal network are likely to conflict with the GP’s goals and negatively influence her/his capacity to accomplish the prescriptive targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N Network clustering coefficient describes the degree of network collectivization [6], that is, it is used to identify whether there is a central tendency in the network. Whole network clustering coefficient is bigger, the network of centralized trend is higher, and the users of public opinion tend to the interaction with small groups [7].…”
Section: Whole Characteristics Evolution Analysismentioning
confidence: 99%
“…Several studies have focused on the role played by social networks on the spread of information between individuals, by making use of email and blog databases and online social networks such as Twitter [11,12] and Facebook [6,7]. Such empirical studies have shown how social networks affect the propagation of health issues [13,14], ideas [15], criminal behavior [16,17], economic decisions [18,19], school achievement [20], and cooperation [21,22], among other human traits.…”
mentioning
confidence: 99%